Hubungan Obesitas, Pantang Makan dan Mobilisasi Dini dengan Penyembuhan Luka Post Sectio Caesarea Hari Ke 7 - Widiarti, Asri; Novita, Astrid (MPI Press, 2024)
Introduction: Healing of the sectio caesarea surgical wound can be influenced by several factors. The factors that affect the wound healing process of post sectio caesarea include nutrition, mobilization, personal hygiene, obesity, medication, and infection. Objectives: This study aims to determine the relationship between obesity, abstinence from eating, and early mobilization with post- sectio caesarea wound healing at Pagelaran Hospital, Cianjur Regency. Method: This type of research is analytical research using a cross-sectional approach. This study involved 96 post-cesarean section mothers at Pagelaran Regional General Hospital. The sampling technique in this study uses an accidental sampling technique. Data collection instrument using a questionnaire. Test data analysis using univariate analysis and bivariate analysis with chi-square statistical test. Result: The results showed a relationship between obesity and post sc wound healing wound healing with a p-value of 0.000 <0.05 and OR 5.971. The relationship of abstinence from eating with wound healing in post SC with p-values of 0.001 <0.05 and OR 4.356. And the relationship between early mobilization and wound healing in post SC wound healing with a p-value of 0.013 <0.05 and OR 3.041. Conclusion: There is a relationship between obesity, abstinence, and early mobilization with post SC wound healing at Pagelaran Hospital, Cianjur Regency.